Analisis Penerapan Sistem Informasi Manajemen pada Kegiatan Logistik di Indonesia - Syehan Sasmito Muslim; Nurcahyo Ageng Wibowo; Faris Nofandi (Politeknik Ilmu Pelayaran Semarang, 2021)
Information systems are devices that are generally used in an organization or company in managing data or information. One of the advantages of this information system is in the search for data information needed by the industry. Logistics activities require an information system that can represent a real situation that contains all activities to expedite logistics activities as well as making logistics policies quickly and accurately. Therefore it is necessary to have an integrated data system to support all logistical activities. The purpose of this study was to analyze the application of management data systems in logistics management. The benefit is to make it easier to solve the problem of delays in sending information data. The method used in this research is descriptive qualitative research. The results of this information search will eventually be stored and then used as a database in the industry so that when the industry requires data retrieval it can be easier to do it quickly and accurately.